Research Progress on Liquid Metal Embrittlement Behavior of Candidate Structural Materials for Lead-Bismuth Reactors - Ma Guobao, Tang Zhengxin, Bao Hansheng, He Xikou (Teshugang)
As one of the fourth-generation nuclear reactors， the Lead-cooled Fast Reactor （LFR） has garnered significant attention owing to the superior thermophysical and neutron properties of the Lead-Bismuth Eutectic （LBE）. However， the compatibility between its structural materials and liquid LBE remains a critical barrier to its advancement. Liquid Metal Embrittlement （LME）， one of the most prominent challenges， markedly diminishes the elongation and fatigue life of structural materials under specific conditions， thereby jeopardizing the safety and reliability of the reactors. This paper focuses on the LME issue in LFR structural materials， elucidating the LME behavior of key candidate structural materials-ferritic/martensitic steel， aluminum-containing ferritic steel， austenitic steel， and aluminum-containing austenitic steel in high-temperature liquid LBE， while clarifying their respective sensitivities to LME of various materials To address this formidable challenge of LME， the paper examines various influencing factors， including temperature， oxygen concentration， strain rate， pre-exposure， and metallurgical state， summarizing the current understanding of how these factors affect LME and their underlying mechanisms. Finally， based on existing research findings， the paper provides an outlook on the future prospects for enhancing the comprehension of the LME mechanism.